KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK KALDU BUBUK LIMBAH TULANG IKAN TENGGIRI (Scomberomorus commerson) PADA BERBAGAI SUHU PENGERINGAN - Fatiha, Nazzwa; Nurimansyah, Nurimansyah; Assrorudin, Assrorudin; Dian Pratiwi Permatahati, Ayu; Indriawan, Rois (Suara UNJA, 2026)
Mackerel fish bones (Scomberomorus commerson) are fishery waste with high calcium content that has the potential as a raw material for organic flavoring, although currently its management is not optimal and has the potential to cause ecological impacts. This study aims to analyze the effect of variations in drying temperature on physicochemical quality and consumer acceptance levels. The methodology applied was a Completely Randomized Design (CRD), which included different temperature and duration variations: 70 ˚C (6 hours), 80 ˚C (4 hours), and 90 ˚C (2 hours). The results showed that the yield value ranged from 16% to 20%, with the highest percentage achieved at a drying temperature of 80 ˚C. All treatments met the national moisture content standard of ≤ 8%. Ash content ranged from 50.96%-54.87% and protein content from 1.13%-2.18%. In organoleptic tests, 90 ˚C was the most preferred temperature in terms of color (4.23) and aroma (4.04) due to the Maillard reaction. However, a temperature of 80 ˚C gave the highest scores for texture (4.23) and taste (4.09). Treatment at 80 ˚C for 4 hours showed the highest descriptive values ​​for quality parameters and panelist acceptance.